2016
DOI: 10.1186/s40425-016-0196-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk analysis of a patient with fulminant autoimmune type 1 diabetes mellitus secondary to combination ipilimumab and nivolumab immunotherapy

Abstract: BackgroundCheckpoint inhibitor immunotherapy is becoming an effective treatment modality for an increasing number of malignancies. As a result, autoinflammatory side-effects are also being observed more commonly in the clinic. We are currently unable to predict which patients will develop more severe toxicities associated with these treatment regimens.Case presentationWe present a patient with stage IV melanoma that developed rapid onset autoimmune type 1 diabetes (T1D) in response to combination ipilimumab an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 41 publications
(45 reference statements)
3
74
1
2
Order By: Relevance
“…With regard to the latter, although existing observations of immune-related toxicity are helpful, most literature reporting autoimmune-associated disease consists of case reports 54,55 , in which, for example, autoantibodies are often not described. Moreover, frequently, autoantibodies are negative when reported and autoimmune disease presents rapidly, as seen with diabetic ketoacidosis and T1D; because subsequent longitudinal data are often not reported, scientists have generally been unable to assess whether autoantibodies, such as GAD-65, ICA-512, and ZnT8, become detectable over time.…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the latter, although existing observations of immune-related toxicity are helpful, most literature reporting autoimmune-associated disease consists of case reports 54,55 , in which, for example, autoantibodies are often not described. Moreover, frequently, autoantibodies are negative when reported and autoimmune disease presents rapidly, as seen with diabetic ketoacidosis and T1D; because subsequent longitudinal data are often not reported, scientists have generally been unable to assess whether autoantibodies, such as GAD-65, ICA-512, and ZnT8, become detectable over time.…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…By contrast, biomarker studies are just beginning to identify patients who are at increased risk for immunotoxicity 71 . A recent SNP analysis of high-risk loci for T1D in a human case of fulminant T1D treated with combination ipilimumab and nivolumab failed to reveal a high-risk genetic profile, and so the role of genetic predisposition is unclear with regard to identifying those who might develop autoimmunity when treated with checkpoint blockade 54 . More accurate predictions of irAEs require the development of better insights into the genetics, epigenetics, and environmental elements that control immunity in both animal models and humans 72 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…Other authors also reported the onset of DM after anti-PD-1 therapy,6 some of them in patients under treatment with nivolumab 3–5 7–17. The time of onset varied between 1 and 48 weeks 5–15 15–23…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, twelve cases of anti-PD-1 therapy-induced type 1 diabetes mellitus with positive islet-related autoantibodies (type 1A) have been reported in the literatures (Table 4) (Hughes et al 2015;Martin-Liberal et al 2015;Mellati et al 2015;Hansen et al 2016;Hofmann et al 2016;Lowe et al 2016;Li et al 2017;Araujo et al 2017;Chae et al 2017). Thyroid dysfunction accompanied by positive thyroid autoantibodies occurred in at least three out of these twelve cases of type 1 diabetes mellitus with positive isletrelated autoantibodies.…”
Section: Discussionmentioning
confidence: 98%
“…Some of the literatures reported cases of insulindependent diabetes mellitus with positive islet-related autoantibodies (type 1A, autoimmune diabetes mellitus) after anti-PD-1 therapy as fulminant type 1 diabetes mellitus (Lowe et al 2016;Araujo et al 2017). But it is difficult to conclude that these cases were typical fulminant type 1 diabetes mellitus because of the presence of positive islet- related autoantibodies.…”
Section: Discussionmentioning
confidence: 99%